The Role of Attention-deficit Hyperactivity Disorder in the Self-perceptions of Children with Emotional and Behavioural Difficulties - Whitley, Jessica; Heath, Nancy; Finn, Cindy (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2008)
AbstractThe present study compared the teacher ratings and self-perceptions of two groups of children with emotional and/or behavioural difficulties: a) Those with attention-deficit hyperactivity disorder (ADHD) and b) those with average or below average levels of hyperactivity and attention. Results showed that the ADHD group was rated more poorly by teachers in academic, social, and behavioural domains. This group also inflated their competency ratings in these domains relative to teacher report more than the comparison group.